Deficiency of a New Protein Associated with Cardiac Syndrome X; Called Adropin. Issue 3 (18th April 2013) - Celik, Ahmet; Balin, Mehmet; Kobat, Mehmet Ali; Erdem, Kenan; Baydas, Adil; Bulut, Musa; Altas, Yakup; Aydin, Suna; Aydin, Suleyman
Summary The pathophysiology of cardiac syndrome X (CSX) is still unclear, but most patients with CSX have endothelial dysfunction. It has been shown that adropin uniquely effects the regulation of endothelial function. The purpose of the study was to evaluate the role of adropin in CSX. Eighty‐six consecutive cardiac syndrome X‐diagnosed patients and 86 age‐sex matched healthy subjects were enrolled into the study. Serum adropin levels, nitrite/nitrate levels were measured in each subject. The adropin levels were significantly lower in patients with CSX than healthy subjects (1.7 ± 0.8 ng/mL and 3.4 ± 1.8 ng/mL, respectively; P < 0.001). The BMI values of patients with CSX were significantly higher than control subjects (28.1 ± 2.4 kg/m2 and 26.0 ± 3.7 kg/m2, respectively; P < 0.001). Plasma nitrite/nitrate levels were lower in patients with CSX than control subjects (15.9 ± 1.6 μmol/L vs. 25.4 ± 2.8 μmol/L, respectively; P < 0.001), and they have a significantly positive correlation with plasma adropin levels (r = 0.463, P < 0.001). In the multiple linear regression analysis, nitrite/nitrate levels, BMI, and adropin were found to be independent risk factors for CSX. A ROC curve is used to identify the ability of adropin levels to predict the cardiac syndrome X. The area under the ROC curve was 0.854 for adropin levels (P = 0.0001). The sensitivity and specificity values of adropin levels were 90.7 and 70.9%, respectively (cut‐off value 2.73). In conclusion, lower serum adropin levels were associated with CSX. Adropin is an independent risk factor for CSX.